Ready-to-use ESL activities for every month of the school year - Josel, Carol A. (West Nyack, N.Y. : Center for Applied Research in Education, 1994)
September: teacher notes and additional activities; Monthly activities, numbers, telling time, days of the week, months of the year, other monthly activities, school related activities, story & related activities. October: colors, shapes, foods and related activities... November...
Keywords: English language; Foreign speakers; Activity programs in education; Activity programs in education; English language -- Study and teaching (Primary) -- Foreign speakers -- Aids and devices